Implementasi Tahfiz Al-Qur’an di SMA Zad International Quranic Boarding School (IQBS) Cianjur - Rika Suryani; Qowaid; Arman Paramansyah (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
Tahfiz Al-Qur'an has an important role and remains relevant in the context of today's life. Therefore, research was conducted on tahfiz Al-Qur'an at one of the educational institutions that implements tahfiz Al-Qur'an in its learning curriculum, namely at ZAD International Quranic Boarding School (IQBS) Cianjur High School. The aim of this research is to determine the implementation of tahfiz Al-Qur'an and its supporting and inhibiting factors. This research is qualitative, data collection was carried out using interviews, observation, and document review. Tahfiz Al-Qur'an is the core of the Islamic Religious Education curriculum at this school. In its implementation, SMA ZAD International Quranic Boarding School (IQBS) has provided reliable human resources such as teaching and education staff, as well as qualified Al-Qur'an tahfiz tutors, adequate facilities and infrastructure, curriculum, methods and evaluation of Al-Qur'an tahfiz Good Qur'an. There are also several supporting and inhibiting factors. There are several follow-up suggestions, including the need to carry out an in-depth analysis of the effectiveness of the tahfiz curriculum applied in memorizing the Al-Qur'an and a daily schedule that is valid for 24 hours, examining parental involvement in supporting children's Al-Qur'an tahfiz process. them and conduct an in-depth study of the supporting and inhibiting factors.